Ecology of salmonids in estuaries around the world: adaptations, habitats, and conservation - Colin D Levings (Toronto: UBC Press, 2016)
"For centuries, biologists have marvelled at how anadromous salmonids--fish that pass from rivers into oceans and back again--survive as they migrate between these two very different environments. Yet, relatively little is understood about what happens to salmonid species (including salmon, steelhead, char, and trout) in the estuaries where they make this transition from fresh to saltwater. This book, written by one of the world's foremost experts on the ecology of salmonids, explains the critical role estuaries play in salmonid survival and recovery."--
Keywords: Salmonidae Adaptation; Salmonidae Habitat; Salmonidae Conservation; Salmonidae; Estuarine Ecology; Fishes Estuaries; Sciences